THE EFFECT OF THE PROBLEM-BASED LEARNING MODEL INTEGRATED WITH ETHNOSCIENCE ON THE CRITICAL THINKING SKILLS OF 10TH GRADE STUDENTS AT SMAN 1 SENTAJO RAYA - Sepriza, Nurul; L, Mariani Natalina; Wahyuni, Resma (Yayasan Amanah Nur Aman, 2025)
ABSTRACT This study was motivated by the low critical thinking skills of students in biology learning. The low critical thinking skills of students are caused by the use of learning models that lack variety and the lack of student concern for the environment. This study aims to determine the effect of the Problem- Based Learning (PBL) model integrated with Ethnoscience on students' critical thinking skills in the subject of environmental change and preservation in class X at SMAN 1 Sentajo Raya. The research used a Quasi-Experimental method with a Pre-test-Post-test Non-Equivalent Control Group Design. The research sample consisted of two classes selected by Random Sampling, namely the experimental class that was given the integrated PBL treatment with Ethnoscience and the control class that used the Discovery Learning model assisted by PowerPoint. The research instruments were critical thinking skills tests and observation sheets. The results showed that the critical thinking skills of students in the experimental class were higher than those in the control class. This was evident from the pretest average score of 42.8 in the experimental class and 39.86 in the control class, and the posttest average score of 80.13 in the experimental class and 67.2 in the control class. Data analysis using an independent sample t-test showed a significance value (2-tailed) of 0.00 < 0.05 with a t-value > t-table, namely 5.545 > 1.994. It can be concluded that the application of the integrated ethnoscience Problem Based Learning model has an effect on students' critical thinking skills in the subject of environmental change and preservation in class X at SMAN 1 Sentajo Raya.